Using communities of practice to study malaysian youths'use of new media - Nurzali Ismail (Universiti Kebangsaan Malaysian, 2013)
The integration of new media technologies into the school curriculum continues to be an important goal for Malaysia. However, despite continuous efforts to integrate digital technologies in schools, students’ use of the media within the formal school context continues to be very limited. Malaysian students’ use of digital technologies out of school also remains unclear. This is due to lack of studies being conducted in this area. Thus, this paper argues that an in-depthstudyshould be conducted during school and out of school in order to understand how Malaysian youths use digital media.Such a study can be carried out by using communities of practice (COP) theoretical perspective. COP enables thoroughanalysis to be conducted pertaining to young people’s technological practices, the communities that they belong to and how practices move and influence one another across the boundary of during school and out of school communities.